Revisiting Fluoride in the Twenty-First Century: Safety and Efficacy Considerations - Duffin, Steve; Duffin, Marcus; Grootveld, Martin (Frontiers in Oral Health, 2022)
Over one hundred years of scientific literature is available which describes the long relationship between dentistry and the many possible applications of fluoride anion (F-) as successful therapeutic strategies. To date, systemic introduction of fluoride via water, milk and salt fluoridation, and fluoride-containing tablets, has been employed. Post-eruption topical fluoride products have also been introduced, such as fluoridated toothpaste, along with fluoride-containing rinses and varnishes. Importantly, a recent addition to the available armamentarium of fluoride therapeutics now exists in the form of metal ion-fluorido adducts, most especially silver(I)-diammine fluoride (SDF). In view of its high level of therapeutic success, very recently this agent was added to the World Health Authority’s (WHO’s) list of essential medicines available for the treatment and prevention of tooth decay (1). Overall, this current state of affairs merits a major review of all these fluoride-containing therapeutic compounds, together with their risks and benefits, both individually and collectively. In this study, a simple graphical tool has been developed for the rapid “on-site” evaluation of fluoride intake with respect to a range of oral healthcare products and body mass index is presented as a gauge of safety for the risk of fluoride toxicity in individual patients. This exposition commences with (a) an account of the history and value of fluoride therapeutics in clinical dentistry, including applications of monofluorophosphate and stannous fluoride; (b) an evaluation of the toxicological activities of fluoride, together with a summary of any reports, albeit very rare ones, arising from its clinically-driven overuse; (c) a history of the development, molecular structure, mechanisms of action, and therapeutic applications of SDF, including a summary of any possible toxic activities and effects arising from silver(I) ion rather than fluoride itself; and (d) the establishment of a working relationship between fluoride exposure and toxicity, with special reference to the instigation of newly-developed tabular/graphical reference guidelines for use by dental clinicians who employ fluoride-rich products in their practices. Particular attention is given to the oral care and treatment options of pediatric patients. In conclusion, applications of this unique monitoring tool may serve as a valuable toxicity guide for dental practitioners.